Affctionate Relationships With Brands: Study of the Consequences of Brand Love with Summer Festivals - Eiriz, Vasco (2016)
This article focus on the concept o brand love, a kind of affectionable, deep and lasting relationship established between consumers and brands, which results in beneficial consequences for firms. Having in mind the growing importance of services and the lack of studies on brand love in the service context, this research defined as object of study the summer festivals in Portugal, major music and entertaining events based on strong brands. More specifically, this article diagnosis the concept of brand love and it identifies the consequences of that consumers' love with summer festivals. It was carried out a questionnaire to the consumers of the main summer festivals in Portugal, which obtained 349 responses. The results show that the word-of-mouth and the active participation of consumers are the main consequences of this kind of relationship based on brand love, while loyalty and willingness to pay a premium-price are less evident consequences. The results of this study suggest that it is essential that brands create emotional bonds with consumers aiming at the developing of brand love. This kind of relationship that causes consumers' active participation and word-of-mouth imply that consumers behave as brand ambassadors, allowing brands to strength its competitive position.